Arterial hypertension in tuberculosis patients: clinical course and pharmaceutical control - N. Yu. Klimenko; N. V. Drobotya; A. A. Kastanayan; V. V. Kaltykova; E. Sh. Guseynova (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To access arterial hypertension (AH) prevalence, pathogenesis, and effectiveness of fixed-dose perindopril and indapamide combination in tuberculosis (TB) patients. Material and methods. In total, 489 case records of patients with TB of various localization were analyzed; 42 patients with TB and AH were examined. Dynamics of 24-hour blood pressure monitoring (BPM) parameters, left ventricular (LV) morphology and function (echocardiography data), vegetative effects on hemodynamics (heart rate variability), and endothelial function (von Willebrand factor level measurement, reactive hyperemia test) were investigated. Results. The rates of AH and TB combination were quite high. These patients were characterized by “non-dipper” and “night-peaker” 24-hour BMP profiles, hypersympathicotonia, LV remodeling, right heart hypertrophy tendency, and endothelial dysfunction. Twelve-week therapy with fixed-dose combination of perindopril (4,0 mg) and indapamide (1,25 mg) was associated with positive dynamics of pathogenetic disturbances in AH and TB patients. Conclusion. AH and TB combination negatively affects cardiovascular system. Treatment with perindopril and indapamide combination provides antihypertensive effect and normalizes main mechanisms of BP regulation.